Mengubah Limbah Menjadi Produk Bernilai Ekonomi: Pelatihan Pembuatan Kerajinan Tangan Dari Limbah Pohon Kelapa - Susanty, Etty; Sylvana, Andi; Susila, Arief Rahman (Civiliza Publishing, 2024)
Senang Hati Village is one of the villages located in Malingping District, Lebak Regency, Banten. This village has a superior product, one of which is coconut trees. The lack of community skills in utilizing existing potential causes coconut waste to have no value, even its selling value is very cheap, so that the surrounding community leaves the waste which can automatically pollute the surrounding environment and become useless waste. This is the main problem in Senang Hati Village, apart from the lack of community knowledge about the benefits of waste, the community has also never received socialization and coaching from the Lebak Regency Tourism and Creative Economy Office. The purpose of this Community Service is to empower the Senang Hati village community to be able to manage and utilize waste so that the waste can have economic value, through coconut waste processing training activities. The solution to the problem used in this community service activity is the Empowerment approach. The strategy used is training and mentoring for the community, especially PKK mothers and Karang Taruna members to develop environmentally friendly and sustainable businesses. The expected output of this PKM activity is to increase the insight and skills of the Senang Hati village community regarding the processing and utilization of coconut tree waste. The results and impacts on partners are the growth of awareness and changes in attitudes to maintain a clean and healthy environment by utilizing waste that has economic potential, intelligently, creatively and innovatively and increasing the economic income of village communities through waste processing activities that have economic value.